O niektórych aspektach urbanizacji terenów wiejskich i przemianach ich funkcji - Zawierucha, Stefan (On Some Aspects of Rural Areas Urbanization and their Functional Transformations, 2008)
In the article the author included a description of the urbanization process of rural areas in the context functional structure's changes. This problem is not new, although essential. The process discussion affects functional structure of rural areas in a very differentiated way. It stimulates brand new functions' crystallization and it does good service to the transformation of hitherto, traditional functions of mentioned areas. In great part it leads to blurring of the criteria of rural and urban areas' differentiation. These changes seem to be indivertible. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 356-363